The Adverse Impact of the COVID-19 Pandemic on Abdominal Emergencies: A Retrospective Clinico-Pathological Analysis - Elena Vissio (MDPI AG, 2021)
The COVID-19 pandemic has caused a worldwide significant drop of admissions to the emergency department (ED). The aim of the study was to retrospectively investigate the pandemic impact on ED admissions, management, and severity of three abdominal emergencies (appendicitis, diverticulitis, and cholecystitis) during the COVID-19 pandemic using 2017–2019 data as a control. The difference in clinical and pathological disease severity was the primary outcome measure while differences in (i) ED admissions, (ii) triage urgency codes, and (iii) surgical rates were the second ones. Overall, ED admissions for the selected conditions decreased by 34.9% during the pandemic (control: 996, 2020: 648) and lower triage urgency codes were assigned for cholecystitis (control: 170/556, 2020: 66/356, p < 0.001) and appendicitis (control: 40/178, 2020: 21/157, p = 0.031). Less surgical procedures were performed in 2020 (control: 447, 2020: 309), but the surgical rate was stable (47.7% in 2020 vs. 44.8% in 2017–2019). Considering the clinical and pathological assessments, a higher percentage of severe cases was observed in the four pandemic peak months of 2020 (control: 98/192, 2020: 87/109; p < 0.001 and control: 105/192, 2020: 87/109; p < 0.001). For the first time in this study, pathological findings objectively demonstrated an increased disease severity of the analyzed conditions during the early COVID-19 pandemic.